Clementine Rose and the Pet Day Diaster - Harvey, Jacqueline (2013)
Will Clementine Rose's first day at school be everything she wants it to be? Clementine Rose is so excited! She's going to start school with her best friends Sophie and Poppy and she can't wait. But when she gets there, instead of the lovely Miss Critchley, her teacher is the much sterner and shoutier Mrs Bottomley. And then there's Angus, a little boy who delights in tormenting her from the moment they first meet. After her first day, Clementine decides school may not be so much fun after all. But the announcement of a Pet Day changes everything. If Lavender the teacup pig can come to school with Clementine, everything will be all right won't it
Keywords: Girls -- Juvenile fiction